Pathological and morphological features of bladder neck sclerosis - Klochay V.V.; Krupin V.N.; Nashivochnikova N.A.; Artifeksova A.A. (Саратовский научно-медицинский журнал, 2011)
The research goal is to estimate a condition of microcirculation in a bladder neck in patients with benign prostatic hyperplasia (BPH) and its value in pathogenesis of bladder neck sclerosis. Materials and methods: Work basis included the analysis of treatment results of 1171 patients with BPH who carried complex examination, operative treatment and further supervision. The basic group was made up of 182 patients with BPH who developed bladder neck sclerosis in the postoperative period. The control group consisted of 200patients with BPH who did not develop the described pathology. clinico-anamnestic, laboratory methods and instrumental studies were used. Results: Disturbance of microcirculation in a bladder neck was considered to be a pathogenetic factor of sclerosis development as one of seri¬ous complications of operative treatment in case of BPH. The presence of microcirculatory disorders was confirmed by histological analysis. Inflammation in the bladder neck should be considered as an aggravating factor. Conclusion: The presence of microcirculatory disorders in the bladder neck in patients with BPH requires preoperative corrective therapy for prevention of sclerosis